ANALISIS NILAI-NILAI MORAL DALAM NOVEL SELIMUT MIMPI KARYA R. ADRELAS - Lase, Priska (Universitas Nias Raya, 2023)
This research is motivated by means of the moral values in the novel Blanket of dreams via R. Adrelas. The reason of this examine is to describe moral values, specifically honesty, discipline, social care, empathy, admire for others, religiosity, independence, and responsibility inside the novel Rompis by way of R. Adrelas's Mimpi. The method used in this studies is a qualitative method with a descriptive research type. primarily based at the effects of the look at, it changed into observed that the values of honesty are suitable, well mannered, honest in work and movements, the price of area, the value of social care, particularly caring for fellow humans, supporting individuals who are more difficult genuinely with out asking for remuneration, the price of empathy, specifically being capable of placed oneself in a function others, to apprehend and sense what others sense, the value of, namely the cost of respecting others, specifically respecting parents and respecting the honour of a female, the cost of religiosity, namely perfection only belongs to God the creator, but our circumstance as humans should in no way forget the writer (God), and in no way judge fellow humans because simplest God has the right to judge, the cost of independence, and the fee of obligation can be achieved thru the tasks given can be executed properly. based totally on the consequences of the study, it can be concluded that the moral values contained within the novel cover Mimpi by using R. Adrelas are proven from conduct, lifestyles lessons, training that may be learned in accordance with the values that exist in society. it's miles advised to readers, they can increase their knowledge and information of moral values in literary works, specially R. Adrelas's clean Dream novel. For future researchers, it's miles hoped that this research may be used as a reference or reference. The researcher also hopes that destiny researchers can continue deeper research, especially the unconventional Blanket of dreams with the aid of R. Adrelas.